Pomological and Olive Oil Quality Characteristics Evaluation under Short Time Irrigation of Olive Trees cv. Chemlali with Untreated Industrial Poultry Wastewater - Oueslati, Amira; Dabbou, Samia; Methneni, Nosra; Montevecchi, Giuseppe; Nava, Vincenzo; Rando, Rossana; Bartolomeo, Giovanni; Antonelli, Andrea; Di Bella, Giuseppa; Ben Mansour, Hedi (Sustainability, 2023)
The aim of this work was the investigation of the effect of wastewater generated from the poultry meat industry on the irrigation of olive trees, during a short time period, in order to evaluate its impact on pomological criteria and olive oil quality. Olive trees were subjected to irrigation with different water qualities: (i) poultry wastewater (PWW), (ii) poultry wastewater diluted with tap water 50:50 (v/v) (PWTWW), (iii) rain-fed cultivation system (control). The results showed that PWTWW contains the optimal mineral proportions, leading to improved pomological criteria. However, the highest significant pulp oil content was obtained using poultry wastewater irrigation (69.51%), while this was 66.71% using diluted poultry wastewater, and 58.03 % for the control. Poultry wastewater irrigation yielded the best results in oil standard quality indices. In addition, an enrichment in oil total polyphenols content was achieved. The oil fatty acid profile was not affected following irrigation with poultry wastewater. Nevertheless, there was a significant increase in the contents of oleic acid and alcohols, accompanied by a decrease in total sterols. However, heavy metals accumulation was observed in both fruits and olive oil. In conclusion, our results suggest that among the three water qualities, poultry wastewater is the best alternative to improve olive oil quality.